2014
DOI: 10.1007/s00213-014-3431-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to global but not local motion processing in long-term ecstasy (MDMA) users

Abstract: These results extend on previous research investigating the long-term effects of illicit drugs on visual processing. Two possible explanations are explored: defuse attentional processes may be facilitating spatial pooling of motion signals in users. Alternatively, it may be that a GABA-mediated disruption to V5/MT processing is reducing spatial suppression and therefore improving global motion perception in ecstasy users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 79 publications
0
7
0
Order By: Relevance
“…Forty-five participants were divided into groups based on their drug use history: 21 controls (no occasions of previous drug use) and 24 drug users (> 20 lifetime occasions of ecstasy use). On the basis of previous research which found no effect of ecstasy on visual processing in participants who had recent amphetamine, cannabis or high polydrug use (Brown et al, 2007;Dickson et al, 2009;White et al, 2013White et al, , 2014, the ecstasy group was further divided on the basis of polydrug use. The group was divided into primary ecstasy users (ecstasy is their primary drug of choice, although they still have some polydrug use, n=18, <60 occasions of other illicit drug use, <200 occasions of cannabis use, due to high volume of cannabis use in all groups), and polydrug ecstasy users (n=6, >60 occasions of other illicit drug use).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-five participants were divided into groups based on their drug use history: 21 controls (no occasions of previous drug use) and 24 drug users (> 20 lifetime occasions of ecstasy use). On the basis of previous research which found no effect of ecstasy on visual processing in participants who had recent amphetamine, cannabis or high polydrug use (Brown et al, 2007;Dickson et al, 2009;White et al, 2013White et al, , 2014, the ecstasy group was further divided on the basis of polydrug use. The group was divided into primary ecstasy users (ecstasy is their primary drug of choice, although they still have some polydrug use, n=18, <60 occasions of other illicit drug use, <200 occasions of cannabis use, due to high volume of cannabis use in all groups), and polydrug ecstasy users (n=6, >60 occasions of other illicit drug use).…”
Section: Participantsmentioning
confidence: 99%
“…In other visual domains, Rizzo et al (2005) found that abstinent ecstasy users had impairments in determination of self-motion from optic flow stimuli compared to controls (who had no illicit drug use in the previous year), but no differences on a task determining structure from motion, both of which involve high-level pooling of motion information. Further, White et al (2014) found that ecstasy users without high polydrug use had significantly lower global motion thresholds than controls, participants with no lifetime use of any illicit drug, indicating increased sensitivity to global motion information, i.e. an increased ability to pool motion signals over a large area, but no differences on a local motion task.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Complex motion processing deficits among abstinent ecstasy consumers have also been identified by others (Rizzo et al, 2005). This work directly contradicts another small scale study using a similar paradigm that has suggested improved motion processing -albeit only in a subset of consumers (White et al, 2014). These effects on basic visual functioning have the potential to contribute to impairments in daily activities reliant on these processes, such as driving.…”
Section: Neurocognitionmentioning
confidence: 71%